A preliminary investigation of the relationship between circulating tumor cells and cancer stem cells in patients with breast cancer - Wang, J.; Cao, M. G.; You, C. Z.; Wang, C. L.; Liu, S. L.; Kai, C.; Dou, J. (Cellular and Molecular Biology, 2012)
In this study, we explored the relationship between the circulating tumor cells (CTC) and the CTC-cancer stem cells (CSC) in the patients with breast cancer. The magnetic-activated cell separation (MACS) method and flow cytometry (FCM) for selection of epithelial cells from the peripheral blood mononuclear cells (PBMC) were used to analyze the enriched epithelial cells that were labeled with anti-cytokeratin(CK)-fluorescein isothiocyanate, anti-CD44-phycoerythrin (PE) and anti-CD24-PE, respectively. The CK+ cells were attributed to CTC and the CK+CD44+ CD24-/low cells were thought as to CTC-CSC in 26 breast cancer patients, respectively. Our results showed the CK+ tumor cells were detected in 19 of 26 patients, with the CK+ tumor cells varying from 0.11% to 5.42 %. The CTC-CSC were identified in 18 of the 19 patients with CTC and the percentage of CTC-CSC in CTC was 19.01%. The results yet suggested the breast cancer patients with high-rate CK+ tumor cells were at the advanced tumor node metastases (TNM) stage III, and the patients with low-rate CK+ cells were at the modest TNM stage I. The difference between the two groups was statistically significant (p<0.001). We concluded that there is a significant relationship between CTC and CTC-CSC, but not among TNM stages, in breast cancer metastasis.